Kontribusi Pendekatan SETS Terhadap Keterampilam Psikomotor Sains Fisika Pada Kelas V SDN 001 Kelayang - Sudrajat, Hendar; Asmar, Dewi Ana Futeri (Jurnal Pilar Sains, 2011)
The purpose of this research is to know the cotribution of physic learning through Sains Enviroment Technology Society (SETS) approach implementation in the result of student psychomotor skill achievement. The subject of this research is 30 students of SDN 001 Kelayang in periode 2008-2009. The chosen of main subject is device of optic. Data is collected by giving the applicative psychomotor test after finishing the subject. The data of this result is analyszed descriptively with consist of; student’s achievement and learning completeness. The result analysis showed the student’s achievement is categorized very hight, learning and material completeness of psychomotor skill is categorized hight.